Assessing students' metacognitive strategies in e-learning and their role in academic performance - Moh Sulthon Amien; Achmad Hidayatullah (Jurnal Inovasi Teknologi Pendidikan, 2023)
The presence of e-learning as a new way of learning in the education system has attracted the interest of researchers worldwide. Nowadays, higher education still uses the e-learning system as a part of the learning method. The important issue in E-learning is how to promote academic performance. Metacognition theory argued that academic performance is determined by students’ metacognitive skills. Through metacognitive skills, students set their own goals, learning, monitoring, and evaluating in e-learning. Less is, however, known about how students involve metacognitive strategies in e-learning in the Indonesian context. Also, there is a scarcity of empirical evidence about the role of metacognitive strategies on academic performance in the Indonesian context. The purpose of this study is to assess students' metacognitive strategies and their impact on academic performance (i.e., engagement and achievement) in the e-learning context. One hundred and fifty students participated in the present study. Descriptive statistics and structural equation modeling were performed for data analysis. The result of this study revealed that students have high skills in metacognitive strategies in e-learning. Our study suggested that metacognitive strategies for self-regulated learning were found to be significantly associated with achievement and engagement in e-learning. In comparison, metacognitive for time and environment was only significantly associated with students' engagement but not with achievements. The contribution of this study to academic practice was explored.